Sustainable Financial Management for Hospitals: A Conceptual Framework (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This paper aims to develop a framework for sustainable financial management in hospitals by integrating economic, social, and environmental sustainability principles. The study identifies best practices in financial management through a literature review and provides guidelines for healthcare administrators and policymakers. Design/Methodology/Approach: This study uses a qualitative approach with literature analysis to develop a framework for sustainable financial management in hospitals, drawing on theoretical frameworks like Triple Bottom Line (TBL) and integrated reporting. Research findings: Findings highlight the importance of value-based care, green hospital initiatives, and equity-driven financial models for long-term financial viability while supporting global sustainability goals, including the United Nations Sustainable Development Goals (SDGs). Theoretical contribution/Originality: Theoretical contributions include adapting sustainability frameworks, such as the TBL and integrated financial reporting, to the hospital sector and aligning financial planning with sustainability objectives. This originality bridges gaps in the existing literature by presenting a unified approach that addresses the complexities of healthcare operations. Practitioner/Policy implication: Practitioner implications suggest that adopting sustainable financial practices can improve hospitals' efficiency, reduce ecological footprints, and promote equitable access, particularly in low-resource settings. Policymakers are encouraged to support these efforts through financial incentives and standardized sustainability frameworks. Research limitation/Implication: The study acknowledges limitations such as the lack of standardized sustainability reporting tools and financial constraints in implementing green and equitable practices. Future research should focus on developing universal sustainability metrics, real-time monitoring tools, and strategies for stakeholder engagement.